Clinical and Radiographic Outcomes of Total Elbow Arthroplasty Using a Semi‐constrained Prosthesis with a Triceps‐preserving Approach over a Minimum Follow‐up Period of 4 Years - Qing Zhang; Ming Xiang; Jin‐song Yang; Fei Dai (Orthopaedic Surgery, 2023)
Objective Complications related to triceps after total elbow arthroplasty (TEA) have become a major surgical concern. The triceps‐preserving approach has the advantage of not disturbing the insertion of triceps but is disadvantaged by the reduced exposure of the elbow joint. The aim of this study was to investigate the clinical and radiological outcomes of TEA with a triceps‐preserving approach and to compare the outcomes of TEA to treat arthropathy with that of TEA to treat acute distal humerus fracture. Methods From January 2010 to December 2018, 23 patients undergoing primary TEAs were retrospectively reviewed with a mean follow‐up time of 92.6 months (range, 52–136 months). Each TEA was performed using the triceps‐preserving approach with a semi‐constrained Coonrad–Morrey prosthesis. Patient demographics, range of motion (ROM), pain visual analogue scale (VAS), and triceps strength (Medical Research Council [MRC] scale) were compared before and after surgery. The Mayo Elbow Performance Score (MEPS), Disabilities of the Arm, Shoulder, and Hand (DASH) score, radiographic outcome, and complications were evaluated at follow‐up. Results In total, seven males and 16 females were included in this study, with a mean age of 66.1 years (range:46–85 years). By the last follow‐up, pain had been significantly relieved in all patients. The average MEPS in the arthropathy group and fracture group were 90.8 ± 10.3 points (range: 68–98 points) and 91.7 ± 0.4 (range: 76–100 points), respectively. The average DASH of the arthropathy group and fracture group was 37.3 ± 18.8 points (range: 18–52 points) and 38.4 ± 20.1 (range: 16–60 points). At the last follow‐up after surgery, the mean flexion arcs in the arthropathy group and fracture group were 100.4° ± 24.1° and 97.8° ± 28.1°, respectively. The mean pro‐supination arcs in the arthropathy group and fracture group were 142.4° ± 15.2° and 139.2° ± 17.5°, respectively. There were no significant differences in clinical outcomes between the two groups (P ≥ 0.05). Triceps strength was normal (MRC grade V) in 15 elbows and good in eight elbows. None of the cases experienced weakness of the triceps strength, infection, periprosthetic fractures, or prosthesis breakage. Conclusions The clinical and radiographical outcomes of TEA with the triceps‐preserving approach were satisfactory in patients with distal humerus fracture, osteoarthritis and rheumatoid arthritis.